(untitled) (UNIZIK Journal of STM Education, 2023)
Academic resilience and emotional intelligence as co-predictors of secondary school students’ performance and attitude towards Physics in Enugu State, Nigeria was investigated. Two research questions and two hypotheses guided the study. Predictive correlation research design was employed in the conduct of the study. The population involved 12,879 Senior Secondary two (SS 2) students offering Physics in the 297 public secondary schools in Enugu State. A sample size of 388 SS2 Physics students were drawn using multi-stage sampling procedure. Three instruments were used for data collection, namely; Simon Cassidy Academic Resilience Scale (ASR-30), the modified Mayer-SaloveyCaruso Emotional Intelligence Scale (MSCEIS) and the modified Fennema-Sherman Physics Attitude Scale (PAS). The unified promotion examination results of SS2 students in 2022/2023 academic year were used to determine the performance scores of the students in Physics. The instruments were validated by three experts from Faculty of Education, Nnamdi Azikiwe University, Awka. The coefficient of reliability was established through Cronbach Alpha method which yielded 0.71 ARS-30, 0.78 for MSCEIS and 0.77 for PAS respectively. The data collected were analyzed using moderated multiple regression analysis. The research questions were answered using the coefficient of determination (R2) in the model table, while significant f-change in the model table were used to test the nullhypotheses at 0.05 alpha level. The findings showed that academic resilience and emotional intelligence jointly predicted attitude of students towards Physics but jointly failed to predict performance of students in Physics among other findings. The study concludes that academic resilience and emotional intelligence jointly affect attitude of students towards Physics. The study recommends that Government through ministry of education and school counsellors should regularly organize workshops and seminars to train teachers and students on the need to develop a high level of academic resilience and emotional intelligence so that students will develop positive attitude towards Physics learning.